In Adult Rats With Polycystic Ovarian Syndrome, Unilateral or Bilateral Vagotomy Modifies the Noradrenergic Concentration in the Ovaries and the Celiac Superior Mesenteric Ganglia in Different Ways - Linares, Rosa; Rosas, Gabriela; Vieyra, Elizabeth; Ramírez, Deyra A.; Velázquez, Daniel R.; Espinoza, Julieta A.; Morán, Carolina; Domínguez, Roberto; Morales-Ledesma, Leticia (Frontiers in Physiology, 2019)
In rats with polycystic ovarian syndrome (PCOS) induced by estradiol valerate (EV) injection, sectioning of the vagus nerve in the juvenile stage restores ovulatory function, suggesting that the vagus nerve stimulates the onset and development of PCOS. We analyzed whether in adult rats, the role played by the vagus nerve in PCOS development is associated with the nerve’s regulation of noradrenergic activity in the celiac superior mesenteric ganglion (CSMG). Ten-day-old rats were injected with corn oil [vehicle (Vh)] or EV (2 mg). At 76 days of age, rats injected with Vh or EV were subjected to sham surgery or the sectioning of one or both vagus nerves (vagotomy). The animals were sacrificed at 80–82 days of age at vaginal estrus smear. Compared to Vh-treated animals, EV-induced PCOS rats showed a lack of ovulation, the presence of follicular cysts, and a high concentration of testosterone, without changes in noradrenaline concentrations in the CSMG or ovaries. In PCOS rats, sham surgery lowered serum testosterone and noradrenaline concentrations in the CSMG but did not restore ovulation. In animals with PCOS, vagotomy lowered testosterone concentrations to a larger degree than in sham-surgery animals. The ovaries of rats with PCOS and vagotomy showed fresh corpora lutea, indicating ovulation. In EV-treated rats with unilateral vagotomy, the concentration of noradrenaline in the CSMG was similar to that in rats with PCOS and sham surgery, which did not ovulate, while in the ovaries of PCOS rats with left or bilateral vagotomy, the noradrenaline concentration was lower than that in sham-surgery-treated animals. Our results suggest that the vagus nerve regulates PCOS development through a different mechanism than the increase in the noradrenergic activity in the CSMG; however, in ovaries, the restoration of ovulation is associated with a decrease in ovarian noradrenaline.